A UiO-66-NH2@ANFs aerogel and its preparation method and application

By efficiently combining UiO-66-NH2 on aramid nanofibers, UiO-66-NH2@ANFs aerogel was prepared, which solved the problems of low loading of existing protective materials and complex methods, and achieved efficient chemical warfare agent degradation and thermal insulation performance, which was suitable for personal protective materials.

CN116656135BActive Publication Date: 2025-07-11TIANJIN POLYTECHNIC UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310114223.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-15
Publication Date
2025-07-11
Estimated Expiration
2043-02-15

AI Technical Summary

Technical Problem

The existing chemical warfare agent protective materials have small loads, single functions, complex load methods and cumbersome detoxification processes, resulting in secondary pollution and high energy consumption.

Method used

UiO-66-NH2@ANFs aerogel was prepared by phosphoric acid treatment on aramid nanofibers and pretreated with 3-aminopropyltrimethylsilane and treated with adipic acid chloride to treat UiO-66-NH2 and aramid nanofibers at room temperature.

Benefits of technology

It realizes high density load on the surface of aramid nanofibers, has high specific surface area, flexibility, high temperature resistance and active degradation functions of chemical warfare agents, and is suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116656135B_ABST
    Figure CN116656135B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of chemical warfare agent protection, and particularly to a UiO-66-NH2@ANFs aerogel, a preparation method thereof, and an application thereof. The UiO-66-NH2@ANFs aerogel comprises UiO-66-NH2 and aramid nanofibers; the specific surface area of the UiO-66-NH2@ANFs aerogel is 320-600 m 2 ·g ‑1 , the average pore diameter is 1-1.4 nm, and the thermal conductivity is 0.26-0.28 W·m ‑1 ·K ‑1 . In the present invention, aramid nanofibers are used as a carrier, and zirconium-based MOF (UiO-66-NH2) is highly densely loaded on the surface of the aramid nanofibers to prepare the UiO-66-NH2@ANFs aerogel, which exhibits low density, high specific surface area, flexibility, high temperature resistance, and an active degradation function for chemical warfare agents (high degradation rate and short half-life time), providing a new research idea for the development of personal protective materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of chemical warfare agent protection, and particularly to a UiO-66-NH2@ANFs aerogel and its preparation method and application. Background Art

[0002] Chemical warfare agents (CWAs) pose a great threat to the environment and human health. Existing protection technologies mainly rely on adsorption materials such as activated carbon and zeolites. However, the contaminated absorbents require a cumbersome detoxification process using neutralization or pyrolysis methods, which have drawbacks such as causing secondary pollution, generating additional chemical waste, and high energy consumption. Therefore, there is a great need to degrade these harmful compounds into harmless chemicals and develop personal protective equipment. Metal-organic frameworks (MOFs), as a new type of porous material, have high porosity, specific surface area, rich and adjustable structures, and have broad application prospects in the fields of sensing, catalysis, gas adsorption and separation, water purification, removal of toxic substances, etc. Among them, zirconium-based metal-organic frameworks can effectively adsorb and efficiently degrade chemical warfare agents due to their good stability and the presence of acidic sites. However, the powder form of MOFs limits their practical applications. Although there are research reports on loading MOFs on textiles, there are still defects such as low loading amount, single function, and complex loading methods. Summary of the Invention

[0003] Based on the above, the present invention provides a UiO-66-NH2@ANFs aerogel and its preparation method and application. By pretreating aramid nanofibers (ANFs) functionalized with phosphoric acid with 3-aminopropyltrimethoxysilane, NH2-ANFs fibers connected by silanol bonds are obtained, and by treating UiO-66-NH2 with adipoyl chloride, reactive acyl chloride groups are generated on UiO-66-NH2, realizing the combination of UiO-66-NH2 and aramid nanofibers at room temperature.

[0004] To achieve the above object, the present invention provides the following solutions:

[0005] One of the technical solutions of the present invention is a UiO-66-NH2@ANFs aerogel, where the UiO-66-NH2@ANFs aerogel includes UiO-66-NH2 and aramid nanofibers; the specific surface area of the UiO-66-NH2@ANFs aerogel is 320 - 600 m 2 ·g -1 , the average pore size is 1 - 1.4 nm, and the thermal conductivity is 0.26 - 0.28 W∙m -1 ∙K -1 .

[0006] The second technical solution of the present invention, the preparation method of the above-mentioned UiO-66-NH2@ANFs aerogel, includes the following steps:

[0007] Step 1: Treat the aramid nanofiber dispersion with phosphoric acid, then wash with water and replace the solvent to obtain a PA-ANFs dispersion; add 3-aminopropyltrimethoxysilane to the PA-ANFs dispersion and stir to obtain an NH2-ANFs dispersion;

[0008] Add adipoyl chloride to the UiO-66-NH2 dispersion and ultrasonicate, then centrifuge, and dry the obtained solid material to obtain UiO-66-NH2-int;

[0009] Step 2: Mix the UiO-66-NH2-int with the NH2-ANFs dispersion and stir to obtain a dispersion containing the UiO-66-NH2@ANFs composite material;

[0010] Step 3: Add a solvent to the dispersion containing the UiO-66-NH2@ANFs composite material to prepare a dispersion with a mass concentration of 0.3% of the UiO-66-NH2@ANFs composite material, then freeze-dry and activate to obtain the UiO-66-NH2@ANFs aerogel (UiO-66-NH2 / ANFs aerogel).

[0011] Regarding the treatment of aramid nanofibers with phosphoric acid in Step 1, the present invention also verified the treatment effects of other acids such as sulfuric acid, hydrochloric acid, and glacial acetic acid on aramid nanofibers. The results showed that only the treatment of aramid nanofibers with phosphoric acid can achieve a high loading amount of UiO-66-NH2 subsequently. When using other acids such as sulfuric acid, hydrochloric acid, and glacial acetic acid to treat aramid nanofibers, the final loading amount of UiO-66-NH2 is very low.

[0012] Further, in Step 1, the concentration of the aramid nanofiber dispersion is 0.04 wt%; the concentration of the phosphoric acid in the aramid nanofiber dispersion is 20 wt% - 25 wt%; the treatment is specifically: treat at 40 °C for 2 hours; replace the solvent with N,N-dimethylformamide.

[0013] Further, in Step 1, the mass ratio of 3-aminopropyltrimethoxysilane to the PA-ANFs dispersion is 1:1; the stirring time is 2 hours.

[0014] Further, in step 1, the UiO-66-NH2 dispersion is specifically an ethyl acetate dispersion of UiO-66-NH2, and the concentration of UiO-66-NH2 in the UiO-66-NH2 dispersion is 4 mg / mL; the molar ratio of adipoyl chloride to UiO-66-NH2 is 12-13:1; the time of ultrasonic treatment is 20 min; the drying is specifically drying at 60 °C for 4 h.

[0015] Further, in step 2, the mass ratio of UiO-66-NH2-int to NH2-ANFs is 1-3:1; the stirring is specifically magnetic stirring for 2 hours.

[0016] Regarding the mass ratio of UiO-66-NH2-int to NH2-ANFs, as the addition amount of UiO-66-NH2-int increases, the loading amount of UiO-66-NH2 increases. When the mass ratio of UiO-66-NH2-int to NH2-ANFs is 3:1, the prepared UiO-66-NH2@ANFs aerogel has the best degradation effect on CWAs. Continuing to increase the mass ratio of UiO-66-NH2-int to NH2-ANFs, such as 4:1, although the loading amount of UiO-66-NH2 will further increase, but at the same time, there will be a problem that the density of UiO-66-NH2 loaded on the fiber surface increases, which is instead not conducive to the degradation of CWAs by the UiO-66-NH2@ANFs aerogel. Therefore, the present invention preferably limits the mass ratio of UiO-66-NH2-int to NH2-ANFs to 1-3:1.

[0017] Further, in step 3, the solvent is a mixture of tert-butanol and water with a mass ratio of 1:10; before freeze-drying, there is also a step of freeze-forming; the activation is specifically keeping warm at 100 °C for 12 h under vacuum conditions.

[0018] The third technical solution of the present invention is the application of the above-mentioned UiO-66-NH2@ANFs aerogel in the preparation of chemical warfare agent protective materials.

[0019] The present invention discloses the following technical effects:

[0020] Using the method of the present invention, the combination of the existing UiO-66-NH2 and aramid nanofibers can be achieved at room temperature, and the MOFs loading amount is high. It has the characteristics of simple method and suitability for large-scale application.

[0021] In the present invention, aramid nanofibers are used as carriers, and zirconium-based MOF (UiO-66-NH2) is highly densely loaded on the surface of aramid nanofibers to prepare UiO-66-NH2@ANFs aerogel, which exhibits low density, high specific surface area, flexibility, high temperature resistance and the function of active degradation of chemical warfare agents (high degradation rate and short half-life time), providing a new research idea for the development of personal protective materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required to be used in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.

[0023] Figure 1 It is the action mechanism of PA treatment of aramid nanofibers in the present invention.

[0024] Figure 2 It is the synthesis route and subsequent digestion of functional UiO-66-NH2 in the present invention.

[0025] Figure 3 It is the preparation flow chart of UiO-66-NH2@ANFs aerogel in the present invention.

[0026] Figure 4 It is the infrared spectrogram of aramid fibers before and after phosphoric acid treatment in the present invention.

[0027] Figure 5 It is the FT-IR diagram (a) and XPS diagram (b) of PA-ANFs and silane-ANFs in the present invention.

[0028] Figure 6 It is the NMR spectra of UiO-66-NH2 and UiO-66-NH2-int in the present invention.

[0029] Figure 7 It is the SEM images of UiO-66-NH2@ANFs-1 (a, b), UiO-66-NH2@ANFs-2 (c, d), UiO-66-NH2@ANFs-3 (e, f) at different magnifications in the present invention.

[0030] Figure 8 It is the TGA diagram of UiO-66-NH2@ANFs aerogel in the present invention.

[0031] Figure 9XRD patterns (a) of UiO-66-NH2 and UiO-66-NH2@ANFs aerogels of the present invention, and FT-IR spectra (b) of ANFs, PA-ANFs and UiO-66-NH2@ANFs aerogels.

[0032] Figure 10 N2 adsorption isotherm (a) and pore size distribution diagram (b) of UiO-66-NH2@ANFs aerogel of the present invention.

[0033] Figure 11 Degradation performance of UiO-66-NH2@ANFs aerogel of the present invention against CEES.

[0034] Figure 12 Degradation rate (a) and half-life (b) of the degradation of CEES by UiO-66-NH2@ANFs aerogel of the present invention.

[0035] Figure 13 Infrared thermal imaging diagrams of ANFs aerogel and UiO-66-NH2@ANFs-3 aerogel prepared in the present invention.

[0036] Figure 14 Infrared thermal imaging temperature curve of UiO-66-NH2@ANFs-3 aerogel of the present invention.

[0037] Figure 15 Thermal conductivity diagram of UiO-66-NH2@ANFs aerogel of the present invention.

[0038] Figure 16 Compression and rebound curve of UiO-66-NH2@ANFs-3 aerogel of the present invention. Detailed Description of the Invention

[0039] Now, various exemplary embodiments of the present invention will be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, characteristics and implementation schemes of the present invention.

[0040] It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention. Additionally, for the numerical ranges in the present invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any intermediate value within any stated value or stated range, as well as each smaller range between any other stated value or intermediate value within the stated range, is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded from the range.

[0041] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. Although this invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein can also be used in the practice or testing of this invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to those documents. In case of conflict with any incorporated document, the content of this specification shall prevail.

[0042] Without departing from the scope or spirit of this invention, various modifications and variations can be made to the specific embodiments of the description of this invention, which are obvious to those skilled in the art. Other embodiments obtained from the description of this invention are obvious to those skilled in the art. The description and examples of this invention are merely exemplary.

[0043] Regarding "comprising", "including", "having", "containing", etc. used herein, they are all open-ended terms, meaning including but not limited to.

[0044] The reagents and equipment used in this invention are all commonly used reagents and equipment in the art without special instructions and can be obtained through purchase.

[0045] As used in this invention, "room temperature" and "normal temperature", without special instructions, both represent 20 - 30 °C.

[0046] The aramid nanofibers used in the examples of this invention are prepared through the following steps:

[0047] (1) Alkali treatment: Weigh a certain amount of sodium hydroxide and dissolve it in distilled water to prepare a 15 wt% alkali solution; add the pre-cut aramid short fibers (AMFs) into the prepared alkali solution according to a bath ratio of 1:250, conduct alkali treatment at a constant temperature of 80 °C for 4 hours, and then perform suction filtration and wash with water until neutral.

[0048] (2) Mechanical treatment: Adjust the alkali-treated fibers to a 0.04 wt% solution, and after treating with a nanofibrillator for 30 cycles, a uniformly dispersed aramid nanofiber dispersion is obtained, denoted as ANFs.

[0049] Aramid nanofiber dispersions obtained through other means such as purchase are also applicable to this invention.

[0050] The UiO-66-NH2 (MOFs) used in the examples of this invention are prepared through the following steps:

[0051] Weigh 0.32 g (1.37 mmol) of zirconium chloride and 0.25 g (1.37 mmol) of 2-aminoterephthalic acid separately and dissolve them in a beaker containing DMF / glacial acetic acid (40 mL / 15.7 mL). Stir magnetically and ultrasonically disperse the mixture for 30 min until the solution becomes transparent. Transfer the mixed solution to a 100 mL polytetrafluoroethylene reaction kettle, place it in a constant temperature drying oven at 120 °C for reaction for 12 h. Take out the reaction kettle, wait until it cools to room temperature and then open the kettle. Pour the reacted solution into a beaker, wash it three times with DMF and methanol respectively, and dry the washed MOF sample at 60 °C for 4 h to obtain UiO-66-NH2 powder, which is bottled and reserved for use.

[0052] UiO-66-NH2 obtained through other means such as purchase is also applicable to the present invention.

[0053] The action mechanism of the PA treatment of aramid nanofibers in the present invention is as Figure 1 shown.

[0054] The synthesis route and subsequent digestion of the functional UiO-66-NH2 in the present invention are as Figure 2 shown.

[0055] The preparation flow chart of the UiO-66-NH2@ANFs aerogel in the present invention is as Figure 3 shown.

[0056] Example 1

[0057] (1) Phosphoric acid pretreatment

[0058] Add phosphoric acid (PA) to the aramid nanofiber dispersion so that the concentration of phosphoric acid in the dispersion is 20 wt% (the technical effects of 20 wt%-25 wt% and 20 wt% are equivalent). Stir at 40 °C for 2 h, then rinse repeatedly with deionized water and replace it with an N,N-dimethylformamide (DMF) system to obtain a PA-ANFs dispersion.

[0059] (2) Pretreatment of aramid fibers with 3-aminopropyltrimethoxysilane

[0060] Weigh 80 mg of the PA-ANFs dispersion pretreated in step (1), and add 80 mg of 3-aminopropyltrimethoxysilane dropwise to the above PA-ANFs dispersion. Stir magnetically at room temperature for 2 h and wash with water 3 times to obtain a dispersion of NH2-ANFs fibers (silane-ANFs) connected by silanol bonds, denoted as the NH2-ANFs dispersion.

[0061] (3) Pretreatment of UiO-66-NH2 with adipoyl chloride

[0062] Weigh 80 mg (0.27 mmol) of UiO-66-NH2 powder and dissolve it in a beaker containing 20 mL of ethyl acetate. Sonicate for 20 min, then add 0.63 g (3.45 mmol) of adipoyl chloride to the system and sonicate for another 20 min. The MOF particles (UiO-66-NH2) turn light yellow. Centrifuge the reacted system at 6000 r / min for 5 min and dry it in an oven at 60 °C for 4 h to obtain UiO-66-NH2-int. Among them, the amino group is chemically modified to an amide group.

[0063] (4)Binding of UiO-66-NH2-int to NH2-ANFs fibers

[0064] Disperse UiO-66-NH2-int at different raw material mass ratios (UiO-66-NH2-int:NH2-ANFs = 1:1, 2:1, 3:1; the prepared aerogels are denoted as UiO-66-NH2@ANFs-1, UiO-66-NH2@ANFs-2, UiO-66-NH2@ANFs-3) in 10 mL, 15 mL, and 20 mL of water, and dropwise add it to the NH2-ANFs dispersion under magnetic stirring at room temperature for 2 h to obtain the UiO-66-NH2@ANFs composite material, abbreviated as the MOF@ANFs composite material.

[0065] (5)Preparation of UiO-66-NH2@ANFs aerogel

[0066] A: Determination of the solid content of the MOF@ANFs composite material

[0067] Take a small part of the sample and weigh it as x g, then dry it in the oven for 2 h and weigh it as y g. Then the measured solid content is y / x%.

[0068] B: Preparation of the dispersion

[0069] Mix tert-butanol and water in a mass ratio of 1:10, and dissolve MOF@ANF to form a dispersion with a mass fraction of 0.3%. The mass of the required MOF@ANF composite material is obtained by multiplying the mass of the tert-butanol and water mixed solution by 0.3% and then dividing by the solid content.

[0070] C: Preparation of the aerogel by freeze-drying

[0071] Put the prepared dispersion into the refrigerator for freezing and then transfer it to a vacuum freeze-dryer for drying. After completion, the UiO-66-NH2@ANFs aerogel sample can be obtained. Put the above aerogel sample into a vacuum oven and vacuum-dry it at 100 °C for 12 h to complete the activation of the MOFs and obtain the UiO-66-NH2@ANFs aerogel.

[0072] The performance of the UiO-66-NH2@ANFs aerogel prepared in Example 1 was tested:

[0073] 1. Surface morphology and structure characterization

[0074] (1)Fourier transform infrared spectroscopy (FT-IR) test

[0075] A Fourier transform infrared spectrometer was used to study the effects of PA treatment on the surface functional groups and chemical structure of aramid fibers. Before the test, aramid and KBr were mixed in a certain proportion, ground thoroughly, and then pressed into a tablet for sample preparation. The test wavelength range was 400 - 4000 cm -1 .

[0076] (2)Scanning electron microscopy (SEM) test

[0077] This characterization instrument can measure the crystal size and morphology and obtain the microscopic surface morphology of the sample. Before observation, the composite aerogel sample was glued to an aluminum sheet with conductive adhesive, and after sputtering with gold, the composite aerogel sample was observed and photographed through a scanning electron microscope.

[0078] (3)X-ray diffraction (XRD) test

[0079] An X-ray diffractometer can perform phase analysis and structure analysis of crystals to determine the crystallinity and phase purity of the material. The ground composite aerogel powder was pressed into a tablet and covered, and then placed into the X-ray diffractometer to test the sample.

[0080] (4)Solid-state nuclear magnetic resonance hydrogen spectrum characterization

[0081] To characterize whether UiO-66-NH2 was functionalized after treatment with adipoyl chloride using liquid nuclear magnetic resonance, 8 - 10 mg of MOF was soaked in 580 μL of DMSOd6 and 20 μL of HF (48% in water) for nuclear magnetic resonance analysis.

[0082] (5)Thermogravimetric analysis characterization

[0083] The sample was placed in an oven at 60 °C for 2 h to remove the residual moisture in the sample. About 10 mg of the sample was weighed and placed in a crucible. At room temperature, in a nitrogen atmosphere, the temperature was increased to 800 °C at a heating rate of 10 °C·min -1 to obtain the thermogravimetric (TG) curve of the sample.

[0084] (6)Specific surface area and pore size characterization

[0085] The samples were tested by a fully automatic specific surface area and porosity analyzer (BET). 30 mg of the membrane samples were taken and crushed into small pieces. After degassing at 200 °C for 3 h in an N2 atmosphere, N2 was adsorbed at 70 K for testing. The adsorption-desorption curves of the samples were obtained, and the specific surface area, pore size distribution curve, etc. of the samples were calculated.

[0086] (7)Characterization by infrared thermal imager

[0087] The test was carried out at room temperature of 25 °C, and the temperature of the heating plate was controlled at 200 °C. The UiO-66-NH2@ANFs aerogel composite and aramid nanofiber aerogel were tested. Two samples with a thickness of 21 mm were placed on the heating plate, and the temperature was raised from room temperature to 200 °C and kept for 30 min. The temperature-time change curve was recorded.

[0088] (8)Thermal conductivity test

[0089] An aerogel obtained by freeze-drying the UiO-66-NH2@ANFs dispersion with a mass concentration of 0.3 and a thickness of 21 mm was used for the thermal conductivity test.

[0090] (9)Compression performance test

[0091] According to the GB / T 1041-92 standard, the compression performance of the aerogel samples was tested using a universal testing machine. During the test, the compression rate was 10 mm·min -1 , and the strain of the aerogel sample was selected as 30% of the overall height of the aerogel for testing. When the strain was 30%, the repeated compression resilience test of the aerogel was carried out, and the number of cycles was 5 times.

[0092] 2. Degradation performance test

[0093] In the aspect of catalytic degradation test, due to the great harm of real chemical warfare agents, their simulants can be used to study the catalytic degradation performance of experimental products. Research shows that the mustard gas simulant CEES has a similar structure and properties to real mustard gas, and the effective degradation of the simulant also has a similar effect on real warfare agents.

[0094] The experimental operation is as follows: First, a glass bottle with a volume of 20 mL is dried at 70 °C for 12 h, and then 40 mg of UiO-66-NH2@ANFs aerogel is placed into it. Then, 5 μL of CEES is introduced into the glass bottle, and it is placed in the dark at room temperature for 10 min, 20 min, 30 min, 1 h, 6 h, 10 h, and 24 h. After the specified time, 2 mL of acetonitrile is added to the glass bottle to extract the reaction products. Then, the liquid phase in the supernatant is sampled with a syringe, and finally, GC testing is carried out. Another 24-h sample is taken for GC-MS testing to determine the generation of products. After GC testing, the peak area under the extraction liquid line can be obtained. According to the linear equation y = 0.004x + 0.0557 (R 2 = 0.9938) between the square root (x) of the peak area under the line and the mass concentration (y, mg / L) of CEES, the mass concentration of CEES after degradation can be calculated. Then, the corresponding degradation rate of CEES is obtained according to the following formula.

[0095]

[0096] In the formula: is the degradation rate of CEES, %; ρ is the mass concentration of CEES after degradation, mg / L; ρ0 is the initial mass concentration of CEES, mg / L.

[0097] The performance test results are as follows:

[0098] 1. Analysis of the structure and morphology of UiO-66-NH2@ANFs aerogel

[0099] 1.1 Analysis of the surface treatment of aramid nanofibers

[0100] In order to enable 3-aminopropyltrimethoxysilane to bond with aramid nanofibers, the inert aramid nanofibers are treated with phosphoric acid to make them carry active groups such as hydroxyl groups. The infrared spectrum of the aramid nanofibers after phosphoric acid treatment is shown in Figure 4 , and the mechanism diagram is shown in Figure 1 .

[0101] The FT-IR and XPS analyses of ANFs after treatment with 3-aminopropyltrimethoxysilane are shown in Figure 5 . 3-aminopropyltrimethoxysilane undergoes hydrolysis and self-condensation to form oligomers, which react with the hydroxyl groups on the fibers to form Si-O-C bonds. At the same time, the epoxy groups on 3-aminopropyltrimethoxysilane also react with the amino groups on the ANFs treated with phosphoric acid to form stable chemical cross-links, as shown in Figure 5 (a). It is the FT-IR spectrum of the aramid fibers after phosphoric acid treatment and after pretreatment with phosphoric acid and then treatment with 3-aminopropyltrimethoxysilane. The 1260 and 897 cm -1The absorption peak at [[]] belongs to the epoxy group in 3-aminopropyltrimethoxysilane. As Figure 5 shown in (b) of , the XPS spectra of aramid fibers treated with phosphoric acid and aramid fibers pretreated with phosphoric acid and then treated with 3-aminopropyltrimethoxysilane are presented. The Si 2s and Si 2p peaks of silicon element in 3-aminopropyltrimethoxysilane are at 154 and 102 eV in the spectra. The FT-IR and XPS analyses indicate that 3-aminopropyltrimethoxysilane has been successfully modified on the aramid nanofibers treated with phosphoric acid.

[0102] 1.2 Analysis of UiO-66-NH2 after treatment with adipoyl chloride

[0103] In order to enable the combination of UiO-66-NH2 and aramid nanofibers treated with 3-aminopropyltrimethoxysilane, the separately synthesized UiO-66-NH2 was pretreated with adipoyl chloride, in which the amino group can be chemically modified to an amide group to obtain UiO-66-NH2-int, as Figure 6 shown in 1 the 1H NMR spectrum, Figure 6 which shows the 1 1H NMR spectrum of UiO-66-NH2 and the 1 1H NMR spectrum of UiO-66-NH2 after functionalization with acyl chloride. As can be seen from Figure 6 it, after acyl chloride functionalization, there is an obvious downfield peak shift, and obvious peaks appear at 11.05 ppm and 9.01 ppm. The chemical shifts at a, b, and c shift from 7.14 ppm, 7.39 ppm, and 7.78 ppm to 7.65 ppm, 9.01 ppm, and 8.03 ppm, namely a', b', and c', which provides strong evidence for the formation of an amide linker by the connection of acyl chloride with the amino group on 2-aminoterephthalic acid. Exposure to fatty acyl chloride for 10 minutes can result in approximately 25% functionalization.

[0104] 1.3 Surface morphology and structure characterization of UiO-66-NH2@ANFs aerogel

[0105] To investigate the loading of UiO-66-NH2-int obtained by pretreating UiO-66-NH2 with adipoyl chloride and aramid nanofibers NH2-ANFs pretreated with 3-aminopropyltrimethoxysilane, the effects of different raw material mass ratios (UiO-66-NH2:ANFs = 1:1, 2:1, 3:1) on the growth effect of MOFs on aramid were studied, and the growth of MOFs in the composite aerogel samples was visualized using SEM and XRD.

[0106] Figure 7SEM micrographs of UiO-66-NH2@ANFs aerogels prepared at different mass ratios under the same 0.3% dispersion concentration. It can be seen from Figure 7 that as the amount of MOFs added increases, the number of crystals formed by the combination of UiO-66-NH2 and ANFs fibers increases significantly. When the mass ratio of ANFs to UiO-66-NH2 is 1:1, the loading of MOFs on the fibers is not ideal, and the MOFs particles grow sparsely on the surface of ANFs. When the mass ratio of ANFs to UiO-66-NH2 is 1:2, the loading of MOFs on the fibers is improved compared to that at 1:1, and the loading amount of MOFs particles on the surface of ANFs increases significantly. When the mass ratio of ANFs to UiO-66-NH2 is 1:3, the growth of MOFs on the fibers is relatively ideal, and they are distributed separately and integrally in the form of particles inside the aerogel.

[0107] As shown in Table 1, for the UiO-66-NH2@ANFs aerogel composites prepared at different mass ratios (UiO-66-NH2:ANFs = 1:1, 2:1, 3:1), by calculating the mass ratio before and after the reaction, the MOF loadings in the three ratios of UiO-66-NH2@ANFs aerogels are 115.5%, 194.5%, and 205.67% respectively.

[0108] Table 1 Loadings at different mass ratios

[0109] Sample Before reaction (g) After reaction (g) Loading amount (%) <![CDATA[UiO-66-NH2@ANFs-1]]> 0.06 0.1293 115.5 <![CDATA[UiO-66-NH2@ANFs-2]]> 0.06 0.1767 194.5 <![CDATA[UiO-66-NH2@ANFs-3]]> 0.06 0.1834 205.67

[0110] In the thermogravimetric analysis (TGA) curve ( Figure 8 ), three main stages are mainly observed in the UiO-66-NH2@ANFs aerogel material: the overall weight loss of the composite material before 100 °C is due to the removal of water and solvents. In the next stage, 320.12 °C is due to the partial decomposition of the organic ligands of UiO-66-NH2. Until the temperature reaches 536.47 °C, the aramid skeleton begins to decompose. At 600 °C, the UiO-66-NH2 skeleton completely collapses. Until 1000 °C, the remaining amounts of UiO-66-NH2@ANFs-1 aerogel, UiO-66-NH2@ANFs-2 aerogel, and UiO-66-NH2@ANFs-3 aerogel are 47.82%, 46.70%, and 41.62% respectively. The greater the loading, the greater the mass loss, which is consistent with the mass loading situation obtained above.

[0111] The crystal structure of the particles on the aramid fibers was characterized using an X-ray diffractometer (XRD). Figure 9Figure (a) shows the XRD comparison diagrams of UiO-66-NH2, UiO-66-NH2@ANFs-1, UiO-66-NH2@ANFs-2, and UiO-66-NH2@ANFs-3. It can be observed from the figure that diffraction peaks appear at 2θ = 7.51° and 8.70° for the UiO-66-NH2@ANFs aerogel, which is consistent with the UiO-66-NH2 powder, confirming that the MOFs in the UiO-66-NH2@ANFs aerogel maintain their original crystal structure and still have the ability to degrade chemical warfare agents. The higher the mass ratio of UiO-66-NH2, the more obvious the peak, indicating that the higher the MOFs loading of the aerogel composite, thus enhancing the degradation of chemical warfare agents. Figure 9 Figure (b) shows the infrared spectra of different mass ratios of ANFs, PA-ANFs, and UiO-66-NH2@ANFs. The stretching vibration peaks of Zr−O are at 655 and 764 cm −1 , Based on the above results, it can be determined that UiO-66-NH2 has successfully grown on the surface of ANFs nanofibers.

[0112] 1.4 Specific surface area and pore structure analysis of UiO-66-NH2@ANFs aerogel

[0113] The specific surface area and porosity of the product were measured by N2 adsorption-desorption isotherms. The specific surface area of UiO-66-NH2@ANFs can be obtained from the N2 adsorption curve in Figure 10 Figure (a). The specific surface areas of UiO-66-NH2@ANFs-1, UiO-66-NH2@ANFs-2, and UiO-66-NH2@ANFs-3 are 320.69 m 2 ·g -1 , 364.12 m 2 ·g -1 , 592.70m 2 ·g -1 , respectively. It can be concluded that with the increase of the mass ratio of UiO-66-NH2, the specific surface area of the UiO-66-NH2@ANFs aerogel increases. The sample UiO-66-NH2@ANFs-3 has the largest physical adsorption capacity for N2 gas, which is consistent with the corresponding SEM images ( Figure 7 ) and XRD analysis ( Figure 9 Figure (a)). The UiO-66-NH2@ANFs aerogel shows a sharp rise at low P / P0, indicating rich micropores. In addition, the pore size distributions of the three samples UiO-66-NH2@ANFs-1, UiO-66-NH2@ANFs-2, and UiO-66-NH2@ANFs-3 are also the same in Figure 10As shown in Fig. (b), it can be seen that the average pore sizes of UiO-66-NH2@ANFs-1, UiO-66-NH2@ANFs-2, and UiO-66-NH2@ANFs-3 are distributed at 1.31 nm, 1.35 nm, and 1.03 nm, respectively.

[0114] 2. Performance of UiO-66-NH2@ANFs Aerogel in Degrading Mustard Gas Simulant

[0115] SEM, XRD, FT-IR, and N2 adsorption isotherm analyses fully demonstrate that UiO-66-NH2 has been successfully loaded onto aramid nanofibers and has a high specific surface area and porosity. The UiO-66-NH2@ANFs aerogel prepared in Example 1 was subjected to a mustard gas simulant degradation test.

[0116] The degradation effect of UiO-66-NH2@ANFs aerogel on the mustard gas simulant CEES is shown in Figure 11 and 12 . From Figure 11 and 12 , it can be seen that after 24 h of degradation, the degradation rates of CEES by UiO-66-NH2@ANFs-3, UiO-66-NH2@ANFs-2, and UiO-66-NH2@ANFs-1 are 96.81%, 95.5%, and 90.98%, respectively, and the degradation half-lives are 16.35 min, 26.17 min, and 47.44 min, respectively. The strong adsorption and degradation ability of UiO-66-NH2@ANFs aerogel mainly relies on the adsorption-hydrolysis principle. Hydroxyl groups are formed on the surface of UiO-66-NH2@ANFs fibers, and then CEES molecules are adsorbed onto UiO-66-NH2@ANFs fibers through hydrogen bonds formed by S and Cl atoms with O groups on the composite material. Subsequently, it is attacked by Zr 4+ , causing the cleavage of the C—Cl bond and hydrolysis. Therefore, as the results show, the more UiO-66-NH2 is added, the higher the loading amount, and the larger the specific surface area, the more favorable it is for gas diffusion and adsorption, effectively increasing the retention time of CEES in the aerogel and greatly facilitating the sufficient time for the reactant and catalyst to adsorb and contact, and the better the degradation effect on CEES. It shows that the UiO-66-NH2@ANFs aerogel prepared in the present invention has a good degradation effect on CEES, and the degradation effect increases with the increase of the UiO-66-NH2 loading amount.

[0117] As shown in Chart 2, the results of various protective materials against chemical weapons reported in the prior art are summarized. It can be seen that the UiO-66-NH2@ANFs aerogel prepared in the present invention has obvious advantages in the degradation of CEES, with a degradation rate of up to 96.81% in 24 hours and a half-life of 16.35 minutes.

[0118] Table 2 Comparison of the degradation of CEES or HD by different catalysts

[0119] Material Mass, mg Agent and dosage, μL Removal rate, % Half-life, min <![CDATA[UiO-66-NH2@ANFs-3]]> 40 CEES, 5 96.81 16.35 UiO-66 40 CEES, 6 84 1.3 <![CDATA[[Cu3(BTC)2]4@chitosan]]> 15 HD, 4 78.2 - MgO@PMIA 20 CEES, 5 70.56 - active carbon plus 11-molybdo-1-vanadophosphoric acid 100 HD, 1 52 - MOF-5 1000 HD, 10 78.1 - active carbon plus sodium phosphotungstic acid (PTANa / C) 100 HD, 1 86 - <![CDATA[polyethyleneimine-H2PV2Mo 10 O 40 > 150 HD, 5 41.5 -

[0120] 3. Thermal insulation performance analysis of UiO-66-NH2@ANFs aerogel

[0121] As an ultra-light porous material, aramid nanofiber aerogel has an ultra-low thermal conductivity equivalent to that of ambient air and excellent thermal insulation performance. Therefore, it can be inferred that the UiO-66-NH2@ANFs aerogel prepared with aramid aerogel as the substrate also has excellent thermal insulation performance. The prepared UiO-66-NH2@ANFs-3 aerogel sample was placed on a heating source (200 °C) to evaluate its thermal insulation performance, and the temperature of the sample surface at different times was recorded. As Figure 13 shown, the surface temperature of the aerogel is much lower than the temperature of the heating plate, and the temperature difference increases with the passage of time. Figure 13 In (a) is the UiO-66-NH2@ANFs aerogel sample, and (b) is the aramid nanofiber aerogel sample. As Figure 13 can be seen, at 5 minutes, the surface temperature of the UiO-66-NH2@ANFs-3 aerogel is 62.2 °C, and the surface temperature of the aramid nanofiber aerogel is 77.6 °C. As time extends, the surface temperature of the sample gradually rises. Until 30 minutes, the surface temperature of the UiO-66-NH2@ANFs aerogel reaches 77.0 °C, and the surface temperature of the aramid nanofiber aerogel reaches 82.6 °C. The heat transfer of porous materials includes heat conduction, heat radiation, and heat convection. Heat is transferred from the bottom of the aerogel material upward through the pores. The UiO-66-NH2@ANFs aerogel with denser pores has a certain blocking effect on the heat transfer compared to the aramid nanofiber aerogel, confirming that the UiO-66-NH2@ANFs aerogel composite material prepared in the present invention has more excellent thermal insulation performance.

[0122] As Figure 14 can be seen from the infrared thermal imaging temperature curve of the UiO-66-NH2@ANFs-3 aerogel, the UiO-66-NH2@ANFs-3 aerogel as a whole has a lower surface temperature than the aramid nanofiber aerogel.

[0123] In addition, the thermal conductivity coefficient reflects the heat conduction ability of the thermal insulation material. Therefore, testing the thermal conductivity coefficient of the aerogel proves its thermal insulation performance. In this invention, the thermal insulation performance of the aerogel is further evaluated by testing the thermal conductivity coefficient of the aerogel material. As Figure 15 shown, the thermal conductivity coefficients of UiO-66-NH2@ANFs-3, UiO-66-NH2@ANFs-2, and UiO-66-NH2@ANFs-1 aerogels are 0.0261 W∙m -1 ∙K -1 , 0.0271 W∙m -1 ∙K -1 and 0.0274 W∙m -1 ∙K -1 respectively, which are significantly lower than the thermal conductivity of aramid nanofiber aerogel, 0.0301 W∙m -1 ∙K -1 . It can be seen that due to the porous network structure inside the UiO-66-NH2@ANFs aerogel and the dense pores introduced by a large number of MOF particles, this material has a low thermal conductivity at room temperature. Moreover, as the MOF loading increases, the thermal conductivity becomes lower and the thermal insulation effect is better.

[0124] 4. Analysis of the compression and rebound performance of UiO-66-NH2@ANFs aerogel

[0125] As a protective material, the UiO-66-NH2@ANFs aerogel prepared in this invention not only requires extremely strong degradation performance but also needs to consider the requirements for the compression performance of this material in practical applications. As Figure 16 shown, it is the compression and rebound curve of the UiO-66-NH2@ANFs-3 aerogel material prepared in Example 1. The height of the used aerogel is 21 mm, the diameter is 27 mm, and the strain is selected as 30% of the overall height of the aerogel for testing. As Figure 16 can be seen, as the stress increases, the strain also increases, and within 5 cycles after the first cycle, this aerogel material maintains good compression and rebound performance.

[0126] The present invention prepares UiO-66-NH2@ANFs aerogel with higher chemical warfare agent degradation performance. UiO-66-NH2 and ANFs are pretreated with adipoyl chloride and 3-aminopropyltrimethylsilane respectively, and UiO-66-NH2 is treated on aramid nanofibers by a post-treatment method to construct a UiO-66-NH2@ANFs aerogel composite material with high adsorption degradation performance, thermal insulation performance and certain mechanical properties. The combination of UiO-66-NH2 and ANFs is studied, the loading amount of UiO-66-NH2 is analyzed, and the degradation performance and degradation mechanism of UiO-66-NH2@ANFs aerogel on mustard gas simulant, as well as the thermal insulation and compression rebound performance are analyzed. The main conclusions are as follows:

[0127] (1) UiO-66-NH2 and ANFs were pretreated with adipoyl chloride and 3-aminopropyltrimethylsilane, respectively, and UiO-66-NH2 was post-treated on aramid nanofibers to construct UiO-66-NH2@ANFs aerogel composites, which had high loading (up to 205.67%) and specific surface area (up to 592.70 m 2 ·g -1 ).

[0128] (2) By changing the mass ratio of UiO-66-NH2 to ANFs, the loading amount of UiO-66-NH2@ANFs nanofiber aerogel can be regulated. As the mass of UiO-66-NH2 added increases, the loading amount also increases.

[0129] (3) The ultra-high porosity of the aramid nanofiber aerogel also makes it highly adsorbable, and it can form a macro-micro dual adsorption effect with UiO-66-NH2, which can increase the contact between the active sites and the CEES molecules. 4+ Under the intensive attack of , the C-Cl bond on CEES breaks quickly and detoxifies by hydrolysis.

[0130] (4) After degradation test analysis, the constructed UiO-66-NH2@ANFs aerogel has good adsorption and degradation effects on mustard gas simulant, with a degradation rate of 96.81% within 24 hours and a half-life of 16.35 minutes. It also has good thermal insulation properties and compression rebound properties, and can be used in the field of gas protection.

[0131] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A UiO-66-NH2@ANFs aerogel, characterized in that, The UiO-66-NH2@ANFs aerogel includes UiO-66-NH2 and aramid nanofibers; the specific surface area of the UiO-66-NH2@ANFs aerogel is 320-600 m 2 ·g -1 , the average pore diameter is 1-1.4 nm, and the thermal conductivity is 0.26-0.28 W·m -1 ·K -1 ; The preparation method of the UiO-66-NH2@ANFs aerogel comprises the following steps: Step 1: Treat the aramid nanofiber dispersion with phosphoric acid, then wash with water and replace the solvent to obtain a PA-ANFs dispersion; add 3-aminopropyltrimethoxysilane to the PA-ANFs dispersion and stir to obtain an NH2-ANFs dispersion; Add adipoyl chloride to the UiO-66-NH2 dispersion and ultrasonicate, then centrifuge, and dry the obtained solid material to obtain UiO-66-NH2-int; Step 2: Mix the UiO-66-NH2-int and the NH2-ANFs dispersion according to a mass ratio of 1-3:1 and stir magnetically for 2 hours to obtain a dispersion containing the UiO-66-NH2@ANFs composite material; Step 3: Add a solvent to the dispersion containing the UiO-66-NH2@ANFs composite material to prepare a dispersion with a mass concentration of 0.3% of the UiO-66-NH2@ANFs composite material, then freeze-dry and activate to obtain the UiO-66-NH2@ANFs aerogel.

2. The UiO-66-NH2@ANFs aerogel according to claim 1, characterized in that, In Step 1, the concentration of the aramid nanofiber dispersion is 0.04 wt%; the concentration of the phosphoric acid in the aramid nanofiber dispersion is 20 wt%-25 wt%; the treatment specifically is: treat at 40 °C for 2 hours; replace the solvent with N,N-dimethylformamide.

3. The UiO-66-NH2@ANFs aerogel according to claim 1, characterized in that, In Step 1, the mass ratio of the 3-aminopropyltrimethoxysilane to the PA-ANFs dispersion is 1:1; the stirring time is 2 hours.

4. The UiO-66-NH2@ANFs aerogel according to claim 1, wherein In Step 1, the UiO-66-NH2 dispersion is specifically an ethyl acetate dispersion of UiO-66-NH2, the concentration of UiO-66-NH2 in the UiO-66-NH2 dispersion is 4 mg / mL; the molar ratio of the adipoyl chloride to UiO-66-NH2 is 12-13:1; the ultrasonication time is 20 min; the drying specifically is drying at 60 °C for 4 h.

5. The UiO-66-NH2@ANFs aerogel according to claim 1, wherein In Step 3, the solvent is a mixture of tert-butanol and water with a mass ratio of 1:10; before freeze-drying, there is also a step of freeze-forming; the activation specifically is heat preservation at 100 °C for 12 h under vacuum conditions.

6. The application of the UiO-66-NH2@ANFs aerogel as described in claim 1 in the preparation of chemical warfare agent protective materials.

Citation Information

Patent Citations

  • Mo / Zr-MOF-loaded aramid fiber denitration sulfur-resistant filter material and preparation method thereof

    CN113058654A

  • Preparation of an HP-UIO-66-NH2 / cellulose composite aerogel material and its application in CO2 adsorption.

    CN114933734A